A wedding for Wiglaf? - McMullan, Kate, 1947-; Basso, Bill. (New York : Grosset & Dunlap, 2003)
When the headmaster of the Dragon Slayers' Academy hears that Princess Belcheena will pay the matchmaker who finds her a husband, he decides that Wiglaf is the perfect candidate
Grades 3-4
Keywords: Princesses -- Fiction; Weddings -- Fiction; Schools -- Fiction; Dragon Slayers' Academy (Imaginary organization) -- Fiction; Children's literature -- 2005